The Elections in Israel, 2019-2021 - Shamir, Michal; Rahat, Gideon (Taylor & Francis, 2023)
The 16th book in The Elections in Israel series, this book covers an extraordinary political event of having four national elections in two years, which were much (but not all) about one person, "King Bibi." Analyzing Israel's national elections from 2019 to 2021, this book argues the four elections became, to a large extent, a referendum on Benjamin Netanyahu, the incumbent prime minister and head of the Likud party, facing investigations, a hearing, and indictment on charges of bribery, fraud, and breach of trust. Thus, the first part of the book is dedicated to political personalization and to Netanyahu himself. The second part of the volume covers the traditional actors in parliamentary elections: voters, parties, and the mass media. The book relies on empirical analysis, including extensive use of the Israel National Election Studies data; on theoretical rigor; and on the contextualization of the elections from comparative and long-term perspectives. The book should interest students and researchers of Israeli politics and society, electoral studies, and the crisis of democracy more generally. Many chapters will be of interest to political science, communications and sociology students and scholars who study themes that are prominent on the academic and public agenda including political personalization and personalized politics, populism, party decline, and democratic backsliding.